PP.22.03: LOW VENOUS COMPLIANCE. (June 2015) - Gonzalez, S.; Martinez, G.; Ricon, D.; Inserra, F.; La Greca, R.; Ramella, I.
Abstract : Objective: Alterations in blood volume management, either by its real expansion or by the volume redistribution from the venous compartment -in a context of low arterial compliance- could be cause of uncontrolled hypertension (UH). a-To evaluate associations between the central blood volume and its redistribution during standing position with blood pressure (BP) b-To determine the prevalence of volume redistribution inhibition during standing in UH c-To identify independent predictors of UH. Design and method: Of 198 subjects evaluated, and after applying exclusion criteria (secondary hypertension, diabetes, kidney disease, adrenergic blockers) 84 were included: 20 normotensives (47.6 ± 9.6 years, 121.8 ± 11.6/73.8 ± 6.1 mm Hg, 37% female) and 64 hypertensives (56.4 ± 12.3 years, 142.3 ± 17.0/84.8 ± 10.5 mm Hg, 44% female) treated with two drugs (RAAS-blockers plus Thiazides or CCB's). BP (ESH) and impedance cardiography were determined, with measurements of thoracic fluid content (TFC: 1/ thoracic impedance, 1/mOhm) in lying/standing positions, besides the total arterial complacency index (TACI, ml/mm Hg) and pre-ejection period (PEP, mseg) as sympathetic tone marker. The lying-standing difference of TFC (TFCdiff, venous redistribution capacity) was calculated. Correlations between TFC/TFCdiff with mean-BP (Pearson) were evaluated. TFCdiff was dichotomized according to sex through a Z-score. Integrating both populations, two groups (+TFCdiff, positive redistribution; -TFCdiff, negative redistribution) were defined, determining their respective prevalences in UH (SBP > 139 mm Hg and/or DBP > 89 mm Hg), (chi2). Finally, UH predictors were assessed by logistic regression. Results: TFC was not associated with mean-BP (r = −0.12, p = 0.27). TFCdiff correlated inversely and significantly with mean-BP (r = −0.34, p = 0.001). Mean values of TFCdiff were 3.1 mOhm in men and 3.7mOhm in women. The prevalence of -TFCdiff was significantly elevated in UH (-TFCdiff: 82.1.% vs. + TFCdiff: 17.9%, p = 0.001). In logistic regression, PEP, TFCdiff, TACI and female sex were independent predictors of UH (image on the following page). Figure. No caption available. Conclusions: We found no relationship between the central blood volume and BP. In contrast, the redistribution of blood volume during standing was inversely and significantly associated with BP. The inability of redistribution of central blood volume was almost constant in uncontrolled hypertensives. A high sympathetic tone, along with low compliances in venous and arteriolar territories, could induce uncontrolled hypertension.